PENGARUH FREE CASH FLOW DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Erma Setiawati; Mujiyati Mujiyati; Erma Marga Rosit (AKUNTABILITAS, 2019)
This research aimed to examine the effect of free cash flow and leverage to earnings management. This study also examines the role of good corporate governance as measured by the index Government in moderating influence of free cash flow and leverage on earnings management. This research was conducted in the company are listed in the Jakarta Islamic Index (JII) from 2015-2017 and unlisted in the Indonesia Stock Exchange. The sample is determined by purposive sampling with 45 samples. This analysis uses regression analysis moderation (MRA). The results of the research indicate where (1) free cash flow significant effect on earnings management, (2) no leverage effect on earnings management, (3) good corporate governance as measured by the index of corporate governance is not able to moderate the influence of free cash flow and earnings management.